Futuristic Integrated Assistive System for Elderly Population of India - C, Mohan; Verma, H.K. (International Journal of Online and Biomedical Engineering (iJOE), 2019)
Elderly population in the world is rising fast and the rise is even faster for India due to the continuous rise in life expectancy. Delivery of health services to the elderly Indian population in rural areas, which is about 80% of the total elderly Indians, is a big challenge. An effective solution to the problem lies in developing assistive systems and devices based on modern technologies and designed to support or assist the elderly persons in having healthy, comfortable and dignified life in the society. This paper presents major challenges of elderly people. Some of the major research works already carried out on assistive systems and devices are summarily reviewed. Some further assistive systems/devices are proposed and desirable features for them are suggested. Novel concept of integrating the proposed assistive systems/devices into a single integrated system to serve the elderly users better is presented.